TRAFFIC CIRCULATION EVALUATION MODEL IN HOSPITAL FACILITY AREA - Intan Pramesti Rochana; Salsabila Shafa Wibowo (Architectural Research Journal, 2024)
Accessibility measures the ease of location to be reached from other locations through the transportation system. Accessibility measures include ease of time, circulation, cost, and effort in moving between places or areas. Therefore, circulation is essential to fulfill this accessibility. This research aims to identify the factors that cause congestion in the accessibility of the Orthopedic and Traumatology Hospital of Surabaya visitors to comfort and analyze the quality and comfort of other road users, especially hospital visitors. This research was conducted using a qualitative descriptive method, which included conducting field observations, direct documentation, and filling out questionnaires with a purposive sampling method. The data collection was obtained by direct observation by describing the factual conditions in the field with the research object, namely the Surabaya Orthopedic & Traumatology Hospital. This study found that the congestion on the road section at intersection 4 of the Citraland area is caused by inefficient circulation, which impacts the accessibility of motorists, especially visitors to the hospital.